Limitation of State Control Rights over Natural Resources in Renewable Energy Management - Ningtias, Ayu Dian; Rochmawanto, Munif; Isnaini, Enik; Cahyani, Nurma (Jurnal Independent, 2024)
Abstract The concept of new energy management policy and renewable energy in maintaining national energy security through the first three properties, private property, namely ownership rights held by individuals or legal entities although it does not mean that it provides private ownership rights over certain natural resources but provides opportunities for individuals to manage natural resources to get certain benefits. Second, common property, namely ownership rights held by groups or can be referred to as "customary rights" in indigenous peoples in Indonesia. Third, state property, namely the right of ownership and control over natural resources is in the hands of the state, with the instrument of "right to control the state". Through government agencies, they can manage their own natural resources as well as SOEs. States can also grant authority to individuals or business entities or cooperatives or communities to manage natural resources.